Polysulfone (PSF) Membrane Incorporated With Polyamide-Tethered Polyhedral Oligomeric Silsequioxane (POSS) For Carbon Dioxide Separation - Tan, Nur Izzati Fitri Zaquan (Universiti Sains Malaysia, 2017)
Carbon dioxide (CO2) is the main contributor to greenhouse effect since industrial revolution. Mixed matrix membrane (MMM) has been introduced to improve the efforts in CO2 removal. Dispersing the porous filler in polymeric matrix can offer dramatic improvement to overcome the tradeoff limitation in between permeability and selectivity of polymeric membrane. In this study, polysulfone MMM incorporated with polyhedral oligomeric silsesquioxane (POSS) were proposed to improve the permeability of CO2. The asymmetric membrane was prepared using phase inversion method for minimum mass transfer resistance. The effects of POSS loading (2.5-5 wt%) on the membrane characteristic and performance were studied. Furthermore, the MMMs were modified using ionic liquid (IL) [emim][TF2N] with 0.4 M concentration and polydimethylsiloxane (PDMS) to improve the gas selectivity of these MMMs. The morphology of the modification with IL by using scanning electron microscopy (SEM) proved the well dispersion of POSS subjected to improve polymer/filler interface and Energy Dispersive X-ray Spectroscopy (EDX) was conducted to detect elemental distributions of membrane surface. Meanwhile Fourier Transform Infrared (FTIR) were also recorded to check the existence bond in the sample. The gas transport properties of all fabricated membranes were investigated using pure gas permeation tests of N2, CO2 and CH4 and further revealed the membrane with 5 wt% of POSS loading, modified by IL and PDMS coating which exhibit satisfactory of CO2/N2 (24) and CO2/CH4 (9).